The origins of Metropolitan Manila a social and political analysis - Caoili, Manuel A. (University of the Philippines Press, 1999)
"The Philippine experience in urbanization and metropolitan growth shows strong similarities to other countries with other Third World countries in Southeast Asia and Latin America. The pattern of Philippine urbanization has its roots in the Spanish colonial era which was continued under American rule. Philippine relations with both these colonial powers were shaped by its role as an early trade center in Asia and as supplier of raw materials and consumer of manufactured goods. Manila, as the direct link between the colony and the colonial power, and as the center of the archipelago's government, economic activities and social life, developed into the dominant, primate city. It was through Manila that modern ideas and institutions as well as foreign capital entered the Philippines which shaped its subsequent development. In this sense, Manila's growth and development promoted the archipelago's socio-economic advancement. At the same time, Manila's expansion into a modern metropolitan area has been nurtured by the wealth of the countryside, that is, its economic as well as human resources, flowing into the city. While Manila rapidly, grew, the rest of the country remained economically stagnant. Viewed from this perspective, the continued existence and growth of Manila as a primate city can hinder equitable development of the country and its in this light that the book examines the problems of Metropolitan Manila."--Back cover.